2003
DOI: 10.1152/ajplung.00445.2002
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia increases AP-1 binding activity by enhancing capacitative Ca2+entry in human pulmonary artery endothelial cells

Abstract: [Ca 2ϩ ]cyt in pulmonary artery endothelial cells (PAEC). Using combined molecular biological, fluorescence microscopy, and biophysical approaches, we examined the effect of chronic hypoxia (3% O 2, 72 h) on AP-1 DNA binding activity, CCE, and transient receptor potential (TRP) gene expression in human (h) PAEC. EMSA showed that AP-1 binding to hPAEC nuclear protein extracts was significantly enhanced by hypoxia, the increase being dependent on storeoperated Ca 2ϩ influx and sensitive to La 3ϩ , an SOC inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
151
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(158 citation statements)
references
References 84 publications
3
151
1
2
Order By: Relevance
“…Ion channels, which can both control and be controlled by E m , therefore are important mediators of the pulmonary vascular response. Indeed, dysfunctional K + channels and upregulated transient receptor potential (TRP) channels have been implicated in the development of idiopathic pulmonary arterial hypertension [9,32,35,36]. Although there is no direct evidence to suggest alterations of Na + channel function in sustained pulmonary vasoconstriction and excessive pulmonary vascular medial hypertrophy in patients with pulmonary arterial hypertension, a recent cDNA microarray study showed that the mRNA expression of the voltage-gated Na + channel β 1 (SCN1B) subunit was increased in lungs tissues from patients with idiopathic and familial pulmonary arterial hypertension [14].…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Ion channels, which can both control and be controlled by E m , therefore are important mediators of the pulmonary vascular response. Indeed, dysfunctional K + channels and upregulated transient receptor potential (TRP) channels have been implicated in the development of idiopathic pulmonary arterial hypertension [9,32,35,36]. Although there is no direct evidence to suggest alterations of Na + channel function in sustained pulmonary vasoconstriction and excessive pulmonary vascular medial hypertrophy in patients with pulmonary arterial hypertension, a recent cDNA microarray study showed that the mRNA expression of the voltage-gated Na + channel β 1 (SCN1B) subunit was increased in lungs tissues from patients with idiopathic and familial pulmonary arterial hypertension [14].…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Based on their amino acid sequence homology, mammalian TRP channels can be divided into six subfamilies, including TRP canonical (TRPC; TRPC1-7), TRP vanilloid (TRPV; TRPV1-6), TRP melastatin (TRPM; TRPM1-8), TRP mucolipin (TRPML; TRPML1-3), TRP ankyrin (TRPA; TRPA1) and TRP polycystin (TRPP; TRPP2, TRPP3, TRPP5) [20]. In general, all seven members of TRPC [2125]; TRPV1, -2, -4 [2628]; all TRPM, except TRPM5 [27] and TRPP1 and -2 [29,30], have been reported to expressed in vascular endothelial cells (ECs) from various sources. TRP channels other than TRPV5, TRPV6, and TRPM1 are found in arterial smooth muscle from different segments of the vasculature [31].…”
Section: Distribution and Functions Of Trp Channelsmentioning
confidence: 99%
“…PAH is thought to be triggered, in this condition, by hypoxia. Although animals are susceptible to high altitude PAH [100,101], most animal model studies of this condition have studied animal responses to hypoxia [102][103][104][105][106][107][108].…”
Section: Principlementioning
confidence: 99%
“…Fantozzi et al [103] showed that hypoxia increased calcium in�ux into human arterial endothelial cells and Remillard and Yuan [99] also implicated increased calcium in�ux. From these and other studies, Fantozzi et al [103] conclude that such calcium in�ux plays a role in "stimulating pulmonary vascular cell proliferation and ultimately, in pulmonary vascular cell remodeling in patients with hypoxia-mediated pulmonary hypertension. "…”
Section: Principlementioning
confidence: 99%
See 1 more Smart Citation